Research on knowledge transfer behaviour in cooperative innovation and simulation - Chenxi Liu (Ekonomska Istraživanja, 2019)
This paper constructs an evolutionary game model of team members’ knowledge transfer behaviour with reciprocal preference in team innovation activities, studies the strategy selection of team members, and simulates the evolution equilibrium strategy of the model with different parameter changes. The results show that the proportion of initial reciprocal actors, the proportion of sharing, and the degree of knowledge complementation are all conducive to the formation of reciprocal cooperation of knowledge transfer, while the work conflict is just the opposite. In addition, the influence of reciprocal preference on evolutionary equilibrium is related to the spreads in reciprocity and self-interested behaviour. This paper extends the research on the reciprocal cooperation of knowledge team from the perspective of behavioural economics.